2021
DOI: 10.1002/cne.25209
|View full text |Cite
|
Sign up to set email alerts
|

Organization and neural connections of the lateral complex in the brain of the desert locust

Abstract: The lateral complexes (LXs) are bilaterally paired neuropils in the insect brain that mediate communication between the central complex (CX), a brain center controlling spatial orientation, various sensory processing areas, and thoracic motor centers that execute locomotion. The LX of the desert locust consists of the lateral accessory lobe (LAL), and the medial and lateral bulb. We have analyzed the anatomical organization and the neuronal connections of the LX in the locust, to provide a basis for future fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(50 citation statements)
references
References 98 publications
(216 reference statements)
0
50
0
Order By: Relevance
“…The GA has been identified as a distinct target area of columnar CL1 neurons connecting slices of the CBL and PB in the fruit fly (Wolff et al, 2015), dung beetles (Immonen et al, 2017), the honeybee (Hensgen et al, 2021a), and the monarch butterfly (Heinze & Reppert, 2012). In the cockroach it is, unlike in the locust (Hensgen et al, 2021b), visible as a distinct area in synapsin staining and was confirmed to be the GA by tracer injection into a single CL1 neuron (Figure 7b). An additional subunit of the LLAL, the PRO, is described here for the first time in an insect.…”
Section: Lateral Complexmentioning
confidence: 85%
See 1 more Smart Citation
“…The GA has been identified as a distinct target area of columnar CL1 neurons connecting slices of the CBL and PB in the fruit fly (Wolff et al, 2015), dung beetles (Immonen et al, 2017), the honeybee (Hensgen et al, 2021a), and the monarch butterfly (Heinze & Reppert, 2012). In the cockroach it is, unlike in the locust (Hensgen et al, 2021b), visible as a distinct area in synapsin staining and was confirmed to be the GA by tracer injection into a single CL1 neuron (Figure 7b). An additional subunit of the LLAL, the PRO, is described here for the first time in an insect.…”
Section: Lateral Complexmentioning
confidence: 85%
“…Heinze & Homberg, 2008; Hensgen et al., 2021a), but their axonal terminals are usually more diffusely distributed throughout the LAL. As targets of various CX outputs, the LALs, as shown in flies, locusts, and silk moths provide input to descending pathways and play an important role in navigational motor control (Hensgen et al., 2021b; Namiki et al., 2018; Rayshubskiy et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Cell bodies were marked using the Landmark module and neuropils were reconstructed as described by Hensgen et al. (2021). Briefly, several layers of each neuropil were manually marked in the x‐, y‐, and z‐plane in the segmentation editor.…”
Section: Methodsmentioning
confidence: 99%
“…The antibody has been used to label synaptic neuropils in different insect species. In S. gregaria, neuropil labeling has been demonstrated by Kurylas et al (2008), el Jundi et al (2010), von Hadeln et al (2018, and Hensgen et al (2021).…”
Section: Antibody Characterizationmentioning
confidence: 99%
See 1 more Smart Citation